Household bargaining and spending on children: Experimental evidence from Tanzania - Charlotte Ringdal; Ingrid Hoem Sjursen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper studies whether increasing the wife's bargaining power results in couples allocating more resources to their child, and, if so, what the underlying mechanisms for this are. We conduct a novel between-subject lab experiment in Tanzania, in which we vary the relative bargaining power between spouses. The paper provides two main insights. First, increasing the wife's bargaining power does not result in an increase in the allocation to the child, but it does lead to equal allocations to boys and girls. Second, time preferences are important; it is more beneficial for the child that the most patient spouse has most bargaining power.
Keywords: C92; D13; J13; O12; 330; intra-household allocation; female bargaining power; Tanzania; Verhandlungsmacht; Frauen; Persönlichkeitspsychologie; Familienökonomik; Experiment; Tansania